Quality standardization of herbal medicines of Spondias dulcis Parkinson using analytical and microbiological analysis - Alencar Fernandes, Felipe Hugo [UNESP]; Boylan, Fabio; Nunes Salgado, Herida Regina [UNESP] (Springer, 2018)
The quality control is vital for the safety and efficacy of herbal medicines. However, the quality of standardization is most difficult because the studies do not cover this step. The objective of this study was quality standardization of herbal drugs of Spondias dulcis Parkinson. The leaves were dried and ground to a powder. The plant drug was evaluated by parameters of mean particle size (417.85m), apparent density (0.37 +/- 0.01gmL(-1)), moisture content (7.96 +/- 0.35%), loss on drying (7.33 +/- 0.09%), pH (3.90 +/- 0.01), total ash (12.66 +/- 0.23%), acid insoluble ash (3.22 +/- 0.20%) and aqueous extractives (24.00 +/- 3.28%). Phytochemical screening revealed the presence of flavonoids and tannins. Microbiological analysis presented a total count within the recommended limits and the absence of pathogenic microorganisms. The infrared spectroscopy (FTIR) and thermal analysis (TG/DTA) showed that physical and chemical processes occurred. The FTIR fingerprint has been characterized by characteristic peaks. The TG curves present six steps, and DTA curve presents three events. The results provide the scientific data for the proper identification and establishment of standards for future investigations and applications.
Keywords: Herbal drugs; Thermoanalytical characterization; Physicochemical characterization